Winter Movements of Bowhead Whales (Balaena mysticetus) in the Bering Sea - Citta, John J.; Quakenbush, Lori T.; George, John C.; Small, Robert J.; Heide-Jørgensen, Mads Peter; Brower, Harry; Adams, Billy; Brower, Lewis (ARCTIC, 2012)
Working with subsistence whale hunters, we tagged bowhead whales (Balaena mysticetus) with satellite-linked transmitters and documented their movements in the Bering Sea during two winters. We followed 11 whales through the winter of 2008 – 09 and 10 whales in 2009 – 10. The average date that bowhead whales entered the Bering Sea was 14 December in 2008 and 26 November in 2009. All but one tagged whale entered the Bering Sea west of Big Diomede Island. In the winter of 2008 – 09, whales were distributed in a line extending from the Bering Strait to Cape Navarin, whereas in 2009 – 10, the distribution shifted south of St. Lawrence Island, extending from Cape Navarin to St. Matthew Island. Bowhead whales were most likely to be found in areas with 90% – 100% sea-ice concentration and were generally located far from the ice edge and polynyas. The average date whales left the Bering Sea was 12 April in 2009 and 22 April in 2010. During the spring migration, all whales but one traveled north along the Alaska coast to summering grounds in the Canadian Beaufort. The remaining whale migrated a month later and traveled up the northern coast of Chukotka, where it was located when the tag stopped transmitting in August. It is unlikely that this whale migrated to the Beaufort Sea before returning south to winter within the Bering Sea, indicating the movements of bowhead whales are more complex than generally believed. Declining sea ice in the Bering Sea may result in the expansion of commercial fisheries and shipping; areas where such activities may overlap the winter range of bowhead whales include the Bering and Anadyr straits, the eastern edge of Anadyr Bay, and St. Matthew Island. Avec l’aide de pêcheurs de baleine de subsistance, nous avons marqué des baleines boréales (Balaena mysticetus) au moyen de transmetteurs en liaison avec un satellite et répertorié leurs mouvements au cours de deux hivers dans la mer de Béring. Nous avons suivi 11 baleines pendant l’hiver 2008-2009 et dix baleines en 2009-2010. En 2008, les ...